2017
DOI: 10.18632/oncotarget.16208
|View full text |Cite
|
Sign up to set email alerts
|

Binding of galectin-1 to integrin β1 potentiates drug resistance by promoting survivin expression in breast cancer cells

Abstract: Galectin-1 is a β-galactoside binding protein secreted by many types of aggressive cancer cells. Although many studies have focused on the role of galectin-1 in cancer progression, relatively little attention has been paid to galectin-1 as an extracellular therapeutic target. To elucidate the molecular mechanisms underlying galectin-1-mediated cancer progression, we established galectin-1 knock-down cells via retroviral delivery of short hairpin RNA (shRNA) against galectin-1 in two triple-negative breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…Based on this evidence, the present study established a predictive model of α-SMA, p-AKT, p-ERK and survivin expression in patients with CRC in order to anticipate the potential intrinsic resistance to the oxaliplatin plus 5-FU regimen. The results from this study demonstrated that α-SMA and survivin overexpression in patients with CRC was significantly associated with oxaliplatin plus 5-FU resistance, which was not the case for p-AKT and p-ERK overexpression; this result was in agreement with previous studies and hypotheses (19,(43)(44)(45). From these different patterns, the model comprising α-SMA, p-AKT, p-ERK and survivin overexpression was the best predictive pattern.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on this evidence, the present study established a predictive model of α-SMA, p-AKT, p-ERK and survivin expression in patients with CRC in order to anticipate the potential intrinsic resistance to the oxaliplatin plus 5-FU regimen. The results from this study demonstrated that α-SMA and survivin overexpression in patients with CRC was significantly associated with oxaliplatin plus 5-FU resistance, which was not the case for p-AKT and p-ERK overexpression; this result was in agreement with previous studies and hypotheses (19,(43)(44)(45). From these different patterns, the model comprising α-SMA, p-AKT, p-ERK and survivin overexpression was the best predictive pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Survivin is a member of the inhibitor of apoptosis proteins family. Numerous studies have demonstrated that survivin overexpression is associated with drug resistance in different cancer types (19,(38)(39)(40). The potential mechanisms involved in survivin overexpression-induced drug resistance are as follows: i) Nuclear survivin serves a pivotal role in the formation of spindle fiber assembly via stabilization of microtubule formation leading to cell growth (41); ii) survivin can upregulate the molecular sensor of DNA damage named ku70 and subsequently enhance the repair of DNA double-stranded breaks (42); and iii) survivin can interact with the apoptosis-inducing molecules caspase-3 and casapase-9 and inhibit their apoptotic function (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from direct tumor cell and ECM interactions, integrins are also known to engage in crosstalk with growth factor receptors, such as EGFR, in the cell-cycle progression in cancer cells. Several studies have implicated that integrin b1 functions during origination, growth, progression, and therapeutic resistance of solid tumors, including GBM and breast cancer with brain metastasis, by promoting stromal and growth factor derived oncogenic signaling (37,38). More recently, downregulation of integrin b1 inhibited mesenchymal function in resistant GBM cells and decreased phosphorylations of EGFR and c-Met in hepatocytes during liver regeneration (6,7,39).…”
Section: Figurementioning
confidence: 99%
“…The GO terminology for the GO enrichment analysis and EC analysis was retrieved from DAVID (http://david.abcc.ncifcrf.gov/). For the GO enrichment analysis, the significant difference of GO enrichment in co-expressed genes was evaluated against a background set consisting of 15,438 genes, at least one of which was derived from a human co-expressed network dataset using hypergeometric distribution. Without multiple test correlations, the BP p-value <0.01 and MF p-value <0.1 were set as significance thresholds.…”
Section: Gene Ontology (Go) and Expression Coherence (Ec)mentioning
confidence: 99%